2021
DOI: 10.1002/acm2.13400
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effect of indirect cell kill in the treatment of multiple brain metastases via single‐isocenter/multitarget volumetric modulated arc therapy stereotactic radiosurgery

Abstract: Due to spatial uncertainty, patient setup errors are of major concern for radiosurgery of multiple brain metastases (m-bm) when using singleisocenter/multitarget (SIMT) volumetric modulated arc therapy (VMAT) techniques. However, recent clinical outcome studies show high rates of tumor local control for SIMT-VMAT. In addition to direct cell kill (DCK), another possible explanation includes the effects of indirect cell kill (ICK) via devascularization for a single dose of 15 Gy or more and by inducing a radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, it should be considered that using wider margins improves quality indices, but increases the risk of necrosis [43] by increasing indicators such as V 12 . The PTV coverage applying translations and rotations was studied and it was shown that dosimetric changes [48] and tumor control [49] followed a complex function of the displacement's combination. This effect may be related to a previous computational work where it was shown that applying rotations in diverse combinations showed different final displacements [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be considered that using wider margins improves quality indices, but increases the risk of necrosis [43] by increasing indicators such as V 12 . The PTV coverage applying translations and rotations was studied and it was shown that dosimetric changes [48] and tumor control [49] followed a complex function of the displacement's combination. This effect may be related to a previous computational work where it was shown that applying rotations in diverse combinations showed different final displacements [16].…”
Section: Discussionmentioning
confidence: 99%
“…Rojas et al derived the optimal planning target volume (PTV) margin required to meet the tolerances [13]. Although there have been evaluations of the target's tumor control probability (TCP) and normal tissue complication probability (NTCP) in the presence of some setup errors, most of those studies performed only physical evaluations [14,15]. Mathematical models have long been used to elucidate physiological and pathological processes in humans, and the models have been extended to many areas of medicine [16,17].…”
Section: Introductionmentioning
confidence: 99%